1993
DOI: 10.1039/c39930000738
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of collectodiol and related polyketide macrodiolides in Cytospora sp. ATTCC 20502: synthesis and metabolism of advanced intermediates

Abstract: The triene 3 and epoxide 6 have been synthesised in specifically labelled form and their incorporation into the macrodiolide, colletodiol 1 demonstrated in cultures of Cytospora sp. ATCC 20502; results of a biomimetic reaction indicate that both colletoketol 2 and grahamimycin A, 7 may be biosynthesised in a single oxidation step from co I I etod i o I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…The required ester 30 eluted first as an oil; (385 mg, 36.8%, 85.2% wrt recovered starting material); vmax/cm-' 1720 and 1655; dH0.O2 (6 H, S, SiCH,), 0.87 (9 H, S, SiCCH,), 1. 13 15.9, 2-H), 5.84 (1 H, m, 2'-H), 6.84 (1 H, dd, J 15.9 and 9.1, 3-H) and 6.95 (1 H, m, 3'-H); m/z (CI, methane) 572 (M', 0.1%), 557 (0.2), 51 1 (I), 475 (3), 413 (6), 359 (8), 337 (25), 271 (59), 212 (45) and 85 (100). This was followed by unreacted alcohol 35 (391 mg, 56.8%).…”
Section: -Methoxyethoxymethy1(2e4r6r)-4-tert-butyldimethylsilox Y Me ...mentioning
confidence: 99%
“…The required ester 30 eluted first as an oil; (385 mg, 36.8%, 85.2% wrt recovered starting material); vmax/cm-' 1720 and 1655; dH0.O2 (6 H, S, SiCH,), 0.87 (9 H, S, SiCCH,), 1. 13 15.9, 2-H), 5.84 (1 H, m, 2'-H), 6.84 (1 H, dd, J 15.9 and 9.1, 3-H) and 6.95 (1 H, m, 3'-H); m/z (CI, methane) 572 (M', 0.1%), 557 (0.2), 51 1 (I), 475 (3), 413 (6), 359 (8), 337 (25), 271 (59), 212 (45) and 85 (100). This was followed by unreacted alcohol 35 (391 mg, 56.8%).…”
Section: -Methoxyethoxymethy1(2e4r6r)-4-tert-butyldimethylsilox Y Me ...mentioning
confidence: 99%
“…As expected, the reaction produced (-)-5-hydroxy-(2E)hexenoic acid, which corresponded to the triketide moiety of the same family of macrodiolides; confirmation of this was obtained from the 1 H NMR spectrum and its specific rotation [6,10]. Previous biosynthetic studies showed that colletodiol (2) was produced from the epoxide derivative (I) induced from the cyclic triene (II), which was formed via cyclization between the C6 precursor (III) and the C8 precursor (IV) [28,29]. Additionally, oxygen-labeling experiments revealed that colletoketol was derived from 2 via the oxidative process [28].…”
Section: Resultsmentioning
confidence: 69%
“…Subsequently, the π-electron at C-9 in the macrodiolide attacked C-6 in the thiosilvatin analogue as a nucleophile, forming a bond between C-9 and C-6' in 1. Next, C-10 in the macrodiolide was attacked by C-3 in the piperazinedione, which Previous biosynthetic studies showed that colletodiol (2) was produced from the epoxide derivative (I) induced from the cyclic triene (II), which was formed via cyclization between the C 6 precursor (III) and the C 8 precursor (IV) [28,29]. Additionally, oxygen-labeling experiments revealed that colletoketol was derived from 2 via the oxidative process [28].…”
Section: Resultsmentioning
confidence: 99%
“…8.21; 163-170), three minor compounds (171)(172)(173) [148], xanthone metabolites (174, 175) [149][150][151][152][153], prenylated benzophenones tenellones A and B (176,177) [154], polyketide metabolites, phaeochromycins A-E (178)(179)(180)(181)(182) [155], and p-terphenyl compounds, named boletopsins A-C (183)(184)(185) and four related compounds (186)(187)(188)(189) [156], were also reported to possess kinase inhibitory activity. 8.21; 163-170), three minor compounds (171)(172)(173) [148], xanthone metabolites (174, 175) [149][150][151][152][153], prenylated benzophenones tenellones A and B (176,177) [154], polyketide metabolites, phaeochromycins A-E (178)(179)(180)(181)(182) [155], and p-terphenyl compounds, named boletopsins A-C …”
Section: Benzoquinones (Table 83)mentioning
confidence: 99%
“…8.26; 211-213), which are produced by S. arenae Tue 469. ATCC 20502 (216) as a potent antimicrobial agent [185,186]. Colletol (214), colletodiol (215), and colletoketol (216) are closely related 14-membered bismacrolactones (Fig.…”
Section: Miscellaneous (Table 86)mentioning
confidence: 99%